Quartz crystal microbalance gas sensor with nanocrystalline diamond sensitive layer. Issue 11 (1st October 2015) - Varga, M.; Laposa, A.; Kulha, P.; Kroutil, J.; Husak, M.; Kromka, A.
Abstract : Gas sensors based on a quartz crystal microbalance (QCM) coated with nanocrystalline diamond (NCD) were developed and tested on NH3, CO2, and humidity detection at room temperature and compared with the bare (uncoated) QCM. NCD films were directly grown on the QCM by a large‐area pulsed linear‐antenna microwave plasma CVD process from the CH4 /CO2 /H2 gas mixture at temperatures below 400 °C. The as‐grown NCD films on QCM and reference Si substrates were characterized by scanning electron and atomic force microscopies as well as Raman and optical spectroscopies. The NCD‐coated QCM gas sensors showed a reasonable performance with a stable repeatability to the tested gases. The response time of the tested diamond‐coated sensor was fast (∼5 s). Moreover, we also observed higher sensitivity and better stability for NCD‐coated QCM than for the bare QCM.